Количественное распределение пелагических остракод (Halocyprididae) в западной части пролива Брансфилда, Антарктика - (:unkn) unknown (My University, 2004)
Анализируется количественное распределение пелагических остракод (сем. Halocyprididae) в западной части пролива Брансфилда на основе зоопланктонных материалов 7-ой Украинской антарктической экспедиции, собранных в марте 2002 г. Максимальная глубина лова варьировала от 200 до 1000 м. Обнаружены восемь видов галоциприд. Три из них доминировали во всем обловленном слое: Metaconchoecia isoheira (44 и 31 % в слоях 0 – 500 и глубже 500 м, соответственно), Alacia belgicae (28 и 23 %) и A. hettacra (24 и 21 %); четвертый – Boroecia antipoda (21 %) – глубже 500 м. Остальные виды (Metaconchoecia skogsbergi, Proceroecia brachiaskos, Discoconchoecia aff. elegans и Conchoecissa symmetrica) встретились в небольшом количестве в нижних слоях облова (200 – 500, 500 – 1000 м). Наибольшие плотность и биомасса галоциприд (>1000 экз./1000 м3 и до 500 – 780 мг/1000 м3 ) наблюдались в слоях 200 – 500 и глубже 500 м. В верхнем 100- метровом слое они были немногочисленны, повышенные величины численности отмечены вдоль фронтальной зоны, формирующейся при взаимодействии вод морей Беллинсгаузена и Уэдделла.
Distribution of pelagic ostracods (Halocyprididae) in the western part of Bransfield Strait, Antarctica
The quantitative distribution of pelagic ostracods (Halocyprididae) in the western part of Bransfield Strait was analyzed based on zooplankton samples collected during the 7th Ukrainian Antarctic Expedition in March 2002. The maximum sampled depth varied from 200 to 1000 m. Eight species of halocyprids were recorded. Three of them were dominant in the whole sampled layer: Metaconchoecia isoheira (44 and 31 % accordingly in the layers 0 - 500 and deeper than 500 m), Alacia belgicae (28 and 23 %) and Alacia hettacra (24 and 21 %); the fourth one - Boroecia antipoda (21 %) - deeper than 500 m. The rest of species ( Metaconchoecia skogsbergi, Proceroecia brachiaskos, Discoconchoecia aff. elegans and Conchoecissa symmetrica) were found not numerous in the deepest sampled layers (200 - 500, 500 - 1000 m). Most abundance and biomass of halocyprids (> 1000 ind./1000 m 3 and up to 500 - 780 mg/1000 m 3 ) was recorded in the 200 - 500 and deeper than 500 m layers. In the 0 - 100 m surface layer they were not numerous, the higher densities of ostracods was marked along the frontal zone formed due to mixture of waters of the Bellingshausen and Weddell seas.
Keywords: пелагические остракоды; Halocyprididae; количественное распределение; пролив Брансфилда; Антарктика